Oxidative Stress And Its Therapeutic Response In Mastitic Cows - Ramesh, P.; Kumari, K.Nalini; Rao, V.Vaikunta; Reddy, V.Padmanabha; Adilaxmamma, K.Adilaxmamma (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
In the present study Mastitic cows were assessed for oxidative stress and antioxidant profile and their response to an antibiotic with (Group III) and without antioxidants (Group II). Affected animals had an insignificantly increased TBARS (Thiobarbituric acid reacting substances), insignificantly decreased GSH and GSH-Px activity, but significantly decreased vitamin-E levels. GSH, GSH-Px and TBARS showed an insignificant change following therapy in both the groups. Vitamin E levels in Group III increased significantly with a better manner of recovery following therapy.